Polysaccharide-Based Magnetic Nanoparticles in Brain Cancer: A Review on the Diagnostic and Therapeutic Potential of Ferumoxytol - Gonzalez, Christian Chapa; Valverde, Pamela Ocampo (Mini Reviews in Medicinal Chemistry, 2025)
Polysaccharide-based iron oxide nanoparticles, particularly PSC-iron oxide nanoparticles, have emerged as promising agents for brain cancer diagnosis and therapy. Originally approved for anemia treatment, PSC-iron oxide nanoparticles leverage extended circulation time, biocompatibility, and MRI contrast capabilities to serve dual diagnostic and therapeutic roles. This review highlights its application in brain tumor management, focusing on enhanced MRI visualization of tumor vascularization and macrophage activity compared to gadolinium-based agents, which improve tumor delineation and treatment monitoring. Additionally, PSC-iron oxide nanoparticles exhibit immune-modulating properties that promote anti-tumor macrophage responses. Preclinical evidence supports the synergistic effects of this approach with existing therapies and its potential in hyperthermia applications. Challenges in clinical translation, including dosage optimization and safety, require further investigation. This review highlights the potential of PSC-iron oxide nanoparticles in current findings to advance precision medicine or nanomedicine approaches for brain tumors.
Keywords: nanomedicine